Voltaiq data format—A standard data format for collection of battery data to enable big data comparisons and analyses across the battery lifecycle - Lininger, Christianna N.; Thai, Tony; Juran, Taylor R.; Leland, Eli S.; Sholklapper, Tal Z. (Frontiers in Energy Research, 2022)
Batteries have enabled modernization of society through portability of electricity. Batteries are also a crucial component to enabling clean technologies of the future such as grid storage and electrified transportation. Because of their ubiquity in modern society, global organizations develop and commercialize batteries for their electrified products. Across the field of battery development, in both commercial and academic settings, there is broad utility in standardization of data formats amongst disparate data sources, labs, equipment, organizations, industries, and lifecycle phases. Due to the way the nascent industry developed, there is a lack of standardization for how performance data is recorded, which is now hindering the industry’s ability to learn from data and accelerate growth. Herein, we describe the different types of data, formats, conventions, and standardization for each phase in the battery lifecycle. Next, we provide a standard data format and conventions for the community to either utilize in their data collection practices or map their existing data into: the Voltaiq Data Format (VDF). This standard data format provides the flexibility needed to capture the variability in data formats and conventions along the battery lifecycle. The utility of this standard format aids in collaboration within and across organizations, accelerating innovation across the industry, and paves the way for the battery community to start utilizing the power of machine learning and data science.